A formação continuada de professoras no contexto da educação infantil - Pezzi, Marcela Fabrícia Velho (My University, 2023)
The present research, entitled "Continuing Education for Teachers in the Context of Early Childhood Education," is linked to the research line "Educational processes, language, technology, and inclusion," as well as to the Education Observatory, specifically to the research line "Teaching, curriculum, and teacher training" of the Graduate Program in Education - PPGEDU-UCS. The central issue addressed was how the processes of continuing education for teachers are constituted in the context of an Early Childhood Education school. The general objective was to investigate the constitutive processes of continuing education for teachers in the context of Early Childhood Education in a school in the city of Caxias do Sul – RS. To answer this issue, three specific objectives were proposed: to understand the context of the Early Childhood Education School and the teachers' perceptions based on continuing education; to map the path of continuing education for teachers working in this Early Childhood Education School; and to identify the conceptions of childhood established in the relationship that teachers establish between professional knowledge and the learning constructed from continuing education. Considering the investigative prism of this study, the theoretical framework included Freire (1991; 2006, 2021), Imbérnon (2009, 2010), Libâneo (2001; 2004, 2007), Nóvoa (1995; 2001; 2002; 2009, 2012), Tardif (2009; 2010, 2014), referring to continuing education. In the field of continuing education in the context of Early Childhood Education, Oliveira-Formosinho (2002) and Barbosa (2018) are considered. Using a qualitative approach (BOGDAN; BIKLEN, 1994), the research methodology was inspired by Action Research (THIOLLENT, 1986). The constructed data were analyzed through Discursive Textual Analysis (DTA) (MORAES; GALIAZZI, 2011). Three continuing education meetings, named Formative Contexts, were proposed to the participating teachers in the research, which, together with the institutional documents of the school, constituted the study corpus. The results indicated little value given to the Pedagogy degree, considered by the teachers as a formation linked to theory without practice. A dichotomy between theory and practice was observed, as teachers seek ready-made strategies in continuing education to face the specificities of teaching in the context of Early Childhood Education, without reflecting on practical action. There was a need for continuous dialogue to achieve a deeper understanding of the child and its relationship with knowledge construction and the pluralities of childhood in the context of Early Childhood Education. A new category of teacher knowledge, the Sensitive Knowledges with Childhood, emerged as a structuring element of a pedagogy of childhood (OLIVEIRA-FORMOSINHO; KISHIMOTO; PINAZZA, 2007). Finally, it was evident that continuing education needs to be carried out in context, observing the specific needs of each group of teachers and each school. [resumo fornecido pelo autor]
A presente pesquisa, intitulada "A Formação Continuada de Professoras no Contexto da Educação Infantil", está vinculada à linha de pesquisa "Processos educacionais, linguagem, tecnologia e inclusão", bem como ao Observatório de Educação, especificamente, à linha de pesquisa "Docência, currículo e formação docente" do Programa de Pós-graduação em Educação – PPGEDU-UCS. A problemática central abordada foi como constituem-se os processos de formação continuada de professoras no contexto de uma escola de Educação Infantil. O objetivo geral consistiu em investigar os processos constitutivos da formação continuada de professoras no contexto da Educação Infantil em uma escola do município de Caxias do Sul – RS. Para responder essa problemática, foram propostos três objetivos específicos: conhecer o contexto da Escola de Educação Infantil e as percepções das professoras a partir da formação continuada; mapear o percurso de formação continuada das professoras que atuam nesta Escola de Educação Infantil; e identificar as concepções de infância instituídas na relação que as professoras estabelecem entre o saber profissional e as aprendizagens construídas a partir da formação continuada. Considerando o prisma investigativo deste estudo, o aporte teórico contou com Freire (1991; 2006, 2021), Imbérnon (2009, 2010), Libâneo (2001; 2004, 2007) Nóvoa (1995; 2001; 2002; 2009, 2012), Tardif (2009; 2010, 2014), ao referirem-se à formação continuada. No âmbito da formação continuada no contexto da Educação Infantil temse Oliveira-Formosinhov (2002) e Barbosa (2018). De abordagem qualitativa (BOGDAN; BIKLEN, 1994), a metodologia de pesquisa teve inspiração na Pesquisaação (THIOLLENT, 1986). Os dados construídos foram analisados através da Análise Textual Discursiva (ATD) (MORAES; GALIAZZI, 2011). Foram propostos às professoras participantes da pesquisa, três encontros de formação continuada, nomeados de Contextos Formativos, que, juntamente com os documentos institucionais da escola, constituíram o corpus do estudo. Os resultados apontaram pouca valorização ao curso de Licenciatura em Pedagogia, considerado pelas professoras uma formação vinculada a teoria sem prática. Constatou-se uma dicotomia entre a teoria e a prática, pois as professoras buscam na formação continuada estratégias prontas para enfrentar as especificidades da docência no contexto da Educação Infantil, não refletindo sobre a ação prática. Evidenciou-se a necessidade de um diálogo contínuo em busca de uma compreensão mais profunda sobre a criança e a sua relação com a construção do conhecimento e as pluralidades de infâncias existentes no contexto da Educação Infantil. Destacou-se uma nova categoria de saber docente, os Saberes Sensíveis com as Infâncias como estruturante de uma pedagogia das infâncias (OLIVEIRA-FORMOSINHO; KISHIMOTO; PINAZZA, 2007). Por fim, evidenciou-se que a formação continuada demanda ser realizada em contexto, observando as necessidades específicas de cada grupo de professores e de cada escola. [resumo fornecido pelo autor]
Keywords: Professores - Formação; Educação de crianças; Escolas - Caxias do Sul (RS); Teachers, Training of; Education of children; Schools - Caxias do Sul (Brazil)